Impact of Islamization towards islamic tourism development in Malaysia - Mahamod, Lukman Hakim; Wan Shamsuddin, Wan Norshafiqah; Wan Yahya, Wan Nur Amirah; Othman, Rashidi; Mohd Hatta, Farah Ayuni; Hashim, Khairusy Syakirin Has-Yun (Yamani Angle Sdn Bhd, 2021)
This paper is concerned with the Islamic tourism movement in Malaysia. The overviews of Islamic tourism chronology in Malaysia can be identified based on the literature review available. In the Malaysia context, Islamic tourism can be defined as any activities, events and experience undertaken in a state of travel that is accordance with the Islamic teaching. This concept is widely discussed among the researchers as a result of the increasing number of Muslim travellers who visit Malaysia after the accident of 9/11 that limited the movement of Muslim traveller in Europe. In addition, this concept growth together with the process of Islamization in Malaysia started in 1982 under the governance of Tun Mahathir Mohamad (Malaysia Prime Minister during the time). Therefore, this paper will focus on the linkage of Islamization evolution with the movement of Islamic tourism in Malaysia as a field of 'dakwah'.